Core journals in dermatology.
Monthly. Current awareness publication "intended to optimize the busy clinician's time by providing a monthly overview of the significant clinically relevant studies in his/her field." Articles appear 4-6 weeks after journal receipt. Foreign journals are also included. Entries give bibliographical information, author's institution and address, and abstract